2007
DOI: 10.1677/joe-07-0238
|View full text |Cite
|
Sign up to set email alerts
|

The influence of di-(2-ethylhexyl) phthalate on steroidogenesis by the ovarian granulosa cells of immature female rats

Abstract: Phthalate esters are known to exert harmful effects on mammalian reproduction and fertility, but their potential adverse effects on the hormonal functions of the ovary have not yet been elucidated in detail. Here, we investigated the effects of di-(2-ethylhexyl) phthalate (DEHP) on the hypothalamic-pituitary-gonadal axis of young developing female rats, as well as on ex vivo steroidogenesis by granulosa cells (GCs) and secretion of LH by gonadotropes. Exposure of 20-day-old female rats to 500 mg DEHP by oral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 20 publications
7
68
0
Order By: Relevance
“…A study in rats described the ability of DEHP (500 mg/kg) to alter ovarian steroidogenesis and production of the gonadotropins by gonadotropes. Specifically, ex vivo production of LH was increased in gonadotropes obtained from DEHP-treated immature rats while serum progesterone levels were decreased (Svechnikova et al 2007). However, a different study showed that inhaled DEHP (5 and 25 mg/m 3 ) increased levels of LH and E 2 in serum of prepubertal rats, and it increased ovarian Cyp19a1 expression (Ma et al 2006), the latter two in disagreement with more recent findings.…”
Section: Plasticizers: Bisphenol a And Phthalatesmentioning
confidence: 55%
“…A study in rats described the ability of DEHP (500 mg/kg) to alter ovarian steroidogenesis and production of the gonadotropins by gonadotropes. Specifically, ex vivo production of LH was increased in gonadotropes obtained from DEHP-treated immature rats while serum progesterone levels were decreased (Svechnikova et al 2007). However, a different study showed that inhaled DEHP (5 and 25 mg/m 3 ) increased levels of LH and E 2 in serum of prepubertal rats, and it increased ovarian Cyp19a1 expression (Ma et al 2006), the latter two in disagreement with more recent findings.…”
Section: Plasticizers: Bisphenol a And Phthalatesmentioning
confidence: 55%
“…Although the mechanism of DEHP-mediated reduction in angiogenesis is not presently clear, this observation may provide evidence for the observed pregnancy complications in females exposed to DEHP, such as anemia, hypertensive disorders and preeclampsia.We determined that the mRNA and protein expression levels of ER␣ and PR were up-regulated by DEHP in the mouse endometrium during the window of implantation. It has also been reported that E2 and P4 are down-regulated by DEHP [41,42]. Since P4 down-regulates the expression level of PR, DEHP would therefore up-regulate PR indirectly during the implantation window.…”
Section: Discussionmentioning
confidence: 97%
“…It is becoming a ubiquitous environmental pollutant with significant human exposure [2,3]. Over the past 20 years, a great deal of research has provided evidence for the serious consequences of DEHP on animal and human health, such as acute toxicity in the liver and kidney [4,5], disruption of the endocrine system [6][7][8] and induction of tumors [5,6]. As an endocrine disruptor (ED), DEHP is known to be severely toxic to the human reproductive system; leading to males retained testicles and disrupted spermatogenesis [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DEHP exposure has been shown to decrease estradiol levels and aromatase levels in vivo [46][47][48] and in vitro [16,49,50]. We have reported that the inhibition of steroidogenesis may be via a direct effect on antral follicle functionality because DEHP exposure in cultured mouse antral follicles directly decreased the availability of precursor sex steroid hormone levels at time points prior to decreasing estradiol levels [51].…”
Section: Introductionmentioning
confidence: 99%